The analyses of the skill of the author in expression of detective elements in the novel “The ABC Murders” - Gulshod Umarboevna, Axmedova; Iroda Odilovna, Shodieva; Azamat Kamariddinovich, Saloxov; Anvar Kulmorodovich, Kurbonov (International Journal of Psychosocial Rehabilitation, 2020)
The article deals with the analysis of the ABC murder and how suspense is depicted in the novel. Suspense is created through almost all elements of a novel, including the title, characters, plot, time restrictions, and word choice. For example, when the plot involves detectives like Hercule Poirot, Inspector Japp, and Captain Arthur Hastings trying to reach an intended victim before a bomb is set to explode, the author has used time restriction as a suspense device.